Effects of home confinement on physical activity, nutrition, and sleep quality during the COVID-19 outbreak in amateur and elite athletes - Taheri, Morteza; Irandoust, Kadijeh; Reynoso-Sánchez, Luis Felipe; Muñoz-Helú, Hussein; Cruz-Morales, Karla Noelia; Torres-Ramírez, Raymundo; Mirmoezzi, Masoud; Youzbashi, Leila; Mirakhori, Fatemeh; Dergaa, Ismail; Vancini, Rodrigo Luiz; Mataruna-Dos-Santos, Leonardo Jose; et al. (Frontiers in Nutrition, 2023)
Despite the progress of the pandemic, it is necessary to continue exploring and explaining how this situation affected the athlete population around the world to improve their circumstances and reduce the negative impact that changes in lifestyle conditions were needed. The aim of this study was to analyze the influence that physical activity, dietary habits, and the experience during the pandemic have on the quality of sleep and the moderating effect that the levels of physical activity and dietary habits have on these relationships. 1,420 elite (40.1%) and amateur (59.9%) athletes (41% women; 59% men) from 14 different countries participated in a cross-sectional design study. Data were collected using a battery of questionnaires that identified sociodemographic data, sleep quality index, physical activity levels, dietary habits, and the athletes' perception of their experience during the COVID-19 pandemic. Means and standard deviation were calculated for each variable. The analysis of variances and correlation between variables were carried out with non-parametric statistics. A simple moderation effect was calculated to analyze the interaction between physical activity or dietary habits on the perception of COVID-19 experience effect over sleep quality in elite and amateur athletes. The physical activity level during Covid-19 was higher for elite athletes (p<.001) and level of physical activity was lower during Covid-19 than pre Covid-19 (p<.01) among amateurs and elite athletes. Also, amateurs had a higher diet quality than elite athletes during the Covid-19 pandemic (p=.014). Only the perception of COVID-19 experience as controllable were significantly higher (p=.020) for elite athletes. In addition, two moderation effects had a significant interaction. For amateur athletes the physical activity level moderates the effect of Controllable COVID-19 experience on sleep quality (F[3,777] =3.05; p=.028), while for elite athletes the same effect was moderated by dietary habits (F[3, 506]=4.47, p=.004). Elite athletes had different lifestyle behaviors compared to amateurs during COVID-19 -ockdown. Furthermore, the relevance of maintaining high levels of physical activity for amateurs and good quality of eating habits for elite athletes is noted by the moderating effect that both variables had on the influence of Controllable experience during the COVID-19 pandemic on sleep quality.